TWO NEW SPECIES OF ACRONYCHIA (RUTACEAE) FROM NEW GUINEA - Hartley, T. G. (REINWARDTIA, 1982)
Two new species of Acronychia from New Guinea,. glauca Hartley and A. loisseliana Hartley, are described and illustrated.